Pengaruh Disiplin Diri dan Kecerdasan Emosional terhadap Prestasi Belajar - Tanti Ardianti; Andi Efendi (Journal of Academia Perspectives, 2021)
This study uses a survey and aims to find and analyze empirically the effect of self-discipline and emotional intelligence together/partially on learning achievement of students SMAN in Indramayu. The sample in this research is 60 students by using simple random sampling techniques. The results showed that: 1) There was a significant effect of self-discipline and emotional intelligence together on learning achievement. This is evidenced by Fcount 22.434 and Sig. = 0.000 < 0.05. 2) There is a significant effect of self-discipline on learning achievement. This is evidenced by tcount = 4.822 and Sig. = 0.000 < 0.05. 3) There is a significant influence of emotional intelligence on learning achievement. This is evidenced by tcount = 3.647 and Sig. = 0.001 < 0.05. This can be interpreted that student learning achievement is influenced by self-discipline and emotional intelligence it has.